Genome-Wide Association Study in a Lebanese Cohort Confirms PHACTR1 as a Major Determinant of Coronary Artery Stenosis - Hager, Jörg; Kamatani, Yoichiro; Cazier, Jean-Baptiste; Youhanna, Sonia; Ghassibe-Sabbagh, Michella; Platt, Daniel E.; Abchee, Antoine B.; Romanos, Jihane; Khazen, Georges; Othman, Raed; Badro, Danielle A.; Haber, Marc; et al. (PLOS ONE, 2012)
The manifestation of coronary artery disease (CAD) follows a well-choreographed series of events that includes damage of arterial endothelial cells and deposition of lipids in the sub-endothelial layers. Genome-wide association studies (GWAS) of multiple populations with distinctive genetic and lifestyle backgrounds are a crucial step in understanding global CAD pathophysiology. In this study, we report a GWAS on the genetic basis of arterial stenosis as measured by cardiac catheterization in a Lebanese population. The locus of the phosphatase and actin regulator 1 gene (PHACTR1) showed association with coronary stenosis in a discovery experiment with genome wide data in 1,949 individuals (rs9349379, OR = 1.37, p = 1.57×10−5). The association was replicated in an additional 2,547 individuals (OR = 1.31, p = 8.85×10−6), leading to genome-wide significant association in a combined analysis (OR = 1.34, p = 8.02×10−10). Results from this GWAS support a central role of PHACTR1 in CAD susceptibility irrespective of lifestyle and ethnic divergences. This association provides a plausible component for understanding molecular mechanisms involved in the formation of stenosis in cardiac vessels and a potential drug target against CAD.